The Preparation and use of Tc-99m metronidazole for cervical cancer imaging - Mdlophane, Amanda Henrietta (University of Limpopo (Medunsa Campus), 2011)
ABSTRACT Introduction: Non-invasive detection of tumour hypoxia theoretically adds value to the. outcome of treatment; however the practical aspect of using 99mTc-EC-MN in cervical cancer remains un-attempted. 99mTc-EC-MN has been used to indirectly detect hypoxia in many tumours (head and neck) and other hypoxic states such as strokes and MI. This study aims to determine the value of using this tracer in early stage cervical cancer. Objectives: This study aimed to investigate the use of 99mTc-EC-MN to determine the degree of hypoxia in cervical cancer. The original study design was to determine whether SPECT with 99mTc-EC-MN would detect ~l'poxi~cervicalc;ancer 'lesions and compare the results with the histological report. The practice of safe handling of radiopharmaceuticals and gaining knowledge in conducting research formed part of the secondary objective of the study. Due to circumstances beyond the control of the researcher, the focus of the study changed from a clinical to a chemistry-based project. Method development: Safety of EC-MN was tested through determination of the labelling efficiency with pertechnetate initially by ITLC-SG. Ethyl acetate, ethanol, saline and ac;etone were selected to develop 99mTc-EC-MN chromatograms to identify the system which best displays separation. Radio-ITLC displayed multiple peaks due to high residual activity in ethyl acetate- and acetone-developed scans. Saline- and ethanol-developed scans showed better separation of 99mTc-EC-MN but separation from free pertechnetate was difficult. Radio HPLC coupled with a diode array detector was used to successfully separate the labelled product, 99mTc-EC-MN from free pertechnetate, thereby achieving good radiolabelling. Clinical application: After the relative safety of the product was established, it was injected IV in the selected patient who had early stage cervical carcinoma. Clinical examinations which included pre-operative WBC, ultrasonography of the kidneys and bladder, and chest x-rays were performed. Histological analysis was performed after surgery and gave results that were insufficient to conclude the absence or the presence of tumour hypoxia. Detection of 99mTc-EC-MN was analysed from blood-flow and -pool images, thyroid and pelvic static, SPECT, and WBS images obtained from a gamma scintillation camera. Faint hot spots consistent with low levels of free pertechnetate were detected in the salivary glands. Hot areas which paralleled the bio-distribution of the 99mTc-EC-MN were also detected in the thyroid, liver, intestines, kidneys, and bladder. There was no tracer detection in the pelvic area. Conclusions: Experience was gained in QC procedures and aseptic preparation of radiopharmaceuticals, and in conducting and co-managing a chemical and clinical based research. Radiochemically related findings demonstrated that tin (II) chloride can be solubilised in water; 99mTc-EC-MN migrates with the solvent front in saline and ethanol developed ITLSG scans; and ITLC cannot sufficiently separate 99mTc-EC-MN from free pertechnetate. Successful labelling of EC-MN was confirmed by scintigraphy and showed tracer distribution that parallels those previously described. Successful labelling of EC-MN with 99mTc can be achieved up to two years after kit manufacture given appropriate storage conditions for the EC-MN. The hypoxic status of the tumour remained inconclusive; therefore the prognostic impact of 99mTc-EC-MN in cervical cancer remains unknown. Recommendations: Product stability and potential expiry should be available for all products, even in the developmental stages and particularly for clinical trials. A simple QC method to separate 99mTc-EC-MN from free pertechnetate should be developed. Further studies are required in order to confirm the efficacy of 99mTc-EC-NM in determining tumour hypoxia in cervical cancer. If a suitable animal model is not available, patients with known cancer tissue hypoxia should be evaluated and compared with those who are non-hypoxic
Thesis(MSc(Med)Pharmacy)) -- University of Limpopo, 2011.
Keywords: Cervical cancer; Tc-99m metronidazole